2012
DOI: 10.1111/jzo.12002
|View full text |Cite
|
Sign up to set email alerts
|

Differences in space use and habitat selection between captive‐bred and wild‐born houbara bustards in Saudi Arabia: results from a long‐term reintroduction program

Abstract: In light of widespread declines of houbara bustard Chlamydotis macqueenii populations across its extant range, captive breeding has emerged as a viable option for regenerating viable populations of houbaras in addition to limiting hunting pressure, habitat management and amelioration of predation pressure. Although reintroductions of captive‐bred houbaras have been carried out in many regions in recent years, information on differences in ranging behavior and habitat selection between captive‐bred and wild‐bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Improvements of habitat selection behavior of captive-bred animals by acclimation training have also been documented by other captive-release studies (e.g. Bright and Morris 1994;Islam et al 2013;Blythe et al 2015).…”
Section: Effect Of Acclimatization On Post-release Habitat Selectionsupporting
confidence: 56%
“…Improvements of habitat selection behavior of captive-bred animals by acclimation training have also been documented by other captive-release studies (e.g. Bright and Morris 1994;Islam et al 2013;Blythe et al 2015).…”
Section: Effect Of Acclimatization On Post-release Habitat Selectionsupporting
confidence: 56%
“…On the other hand, Jabal Khurse is a rounded hill and low in vegetation density that is more suitable for bird display. This result is in line with [18][19][20] as they reported that vegetation heights of less than a meter were found to be the "preferred daytime habitats" for the species in the reserve.…”
Section: Tribulus Arabicussupporting
confidence: 78%
“…In contrary, Jabal Khurse and Rumrumiyya were used for male display and foraging sites, respectively. Such sites were called "preferred habitats" [18,20,21].…”
Section: Tribulus Arabicusmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, the current status of wild resident houbara populations is poorly known (BirdLife International 2016), with the latest studies on population trends conduc ted in the late 1990s (Seddon & van Heezik 1996). More recent studies have examined nest site selection in Iran (Aghanajafizadeh et al 2012) and reintroduced populations in Saudi Arabia (Islam et al 2013) and the United Arab Emirates (UAE) (Azar et al 2016), focusing on survival, densities or habitat selection, but none have examined population breeding parameters. Available data on the breeding parameters of wild populations are also limited, outdated, based on small samples or mainly concern the migrant populations (Table 1).…”
Section: Introductionmentioning
confidence: 99%